On magnetometer heading updates for inertial pedestrian navigation system - Abdulrahim, Khairi; Seman, K.; Othman, M; Md Shuib, F. M.; Moore, Terry; Hide, Christopher; Hill, Chris (Springer, 2014)
A magnetometer is often used to aid heading estimation of a low-cost Inertial Pedestrian Navigation System (IPNS) without which the latter will not be able to accurately estimate heading for more than a few seconds, even with the help of Zero Velocity Update (ZVU). Heading measurements from the magnetometer are typically integrated with gyro heading in an estimation filter such as Kalman Filter (KF) — to best estimate the true IPNS heading, resulting in a better positioning accuracy. However indoors the reliability of these measurements is often questionable because of the magnetic disturbances that can disrupt the measurements. To solve this problem, a filtering method is often used to select the best measurements. However, the importance of the frequency of these measurement updates has not been highlighted.